Comparative Marketing Costs for FCOJ from Florida and Sao Paulo - Ronald P. Muraro; Thomas H. Spreen (EDIS)
The states of Sao Paulo (Brazil) and Florida are the two dominant orange juice producing regions in the world. These two states collectively account for approximately 85 percent of the world's orange juice production. The market orientation of these two regions, however, is quite different. This is EDIS document FE363, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.